Integrating buprenorphine maintenance therapy into federally qualified health centers: real-world substance abuse treatment outcomes. - Haddad, Marwan S; Zelenev, Alexei; Altice, Frederick L (Drug and alcohol dependence, 2013)
Few studies have examined real-world effectiveness of integrated buprenorphine maintenance treatment (BMT) programs in federally qualified health centers (FQHCs).
Keywords: Adult; Buprenorphine; Cohort Studies; Connecticut; Female; Humans; Longitudinal Studies; Maintenance Chemotherapy; Male; Middle Aged; Opioid-Related Disorders; Patient Protection and Affordable Care Act; Retrospective Studies; Substance Abuse Treatment Centers; Treatment Outcome; Young Adult